Effects of a Self-Management Telehealth Program on Improving Strength and Hand Function in Systemic Sclerosis Patients: A Randomized Controlled Trial - Orathai Wantha; Ajanee Mahakkanukrauh; Siraphop Suwannaroj; Kwankaew Tuydaung; Nonglak Methakanjanasak; Kannika Srichomphu; Jinnaphat Kraipoj; Chingching Foocharoen (Life)
Objective: A self-management telehealth program to improve hand strength and function in systemic sclerosis (SSc) patients may improve their quality of life, so we investigated its efficacy. Methods: A 6-week prospective randomized controlled study was conducted in adults with SSc with a hand mobility in scleroderma (HAMIS) score > 1 or a limited range of motion in at least one hand joint. Participants were randomly allocated into three groups for six weeks of health education: (a) typical education, (b) watching video guides as needed, in addition to typical education, and (c) watching video guides and receiving weekly telephone notifications, in addition to typical education. The endpoints were the differences in self-management behavior, HAMIS scores, hand grip strength (HGS), and quality of life (QoL) using the European Quality of Life-5 Dimensions between groups, as well as the changes in these parameters compared to baseline. Results: A total of 24 patients per group were enrolled, with the majority diagnosed with diffuse cutaneous SSc (79.2%). Six weeks post-intervention, HGS improved significantly in both the video guide and telephone notification groups compared to typical education in both hands (p = 0.028, p = 0.044). Pincer grip differed between the groups in the non-dominant hand. Household modifications were more frequent in the video guide and telephone notification groups than in the typical education group (p = 0.023). All groups showed significant improvements in HGS and HAMIS scores in both hands, as well as in self-management behaviors, compared to baseline. QoL, as measured using a visual analog scale, improved significantly after the intervention in both the video guide and telephone notification groups, but not in the typical education group. Conclusions: Self-management telehealth programs effectively enhance hand strength, function, and self-management behaviors in patients with SSc with limited hand function. Weekly telephone notifications further reinforced continuity and engagement in these patients.